2021
DOI: 10.1016/s1473-3099(21)00072-4
|View full text |Cite
|
Sign up to set email alerts
|

Sources of persistent malaria transmission in a setting with effective malaria control in eastern Uganda: a longitudinal, observational cohort study

Abstract: Background Symptomatic malaria cases reflect only a small proportion of all Plasmodium spp infections. Many infected individuals are asymptomatic, and persistent asymptomatic Plasmodium falciparum infections are common in endemic settings. We aimed to quantify the contribution of symptomatic and asymptomatic infections to P falciparum transmission in Tororo, Uganda.Methods We did a longitudinal, observational cohort study in Tororo district, Uganda. We recruited participants of all ages from randomly selected … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
135
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 123 publications
(152 citation statements)
references
References 30 publications
15
135
2
Order By: Relevance
“…The prevalence of malaria in this cohort is similar to population-level regional estimates in the country, as shown by studies that used molecular methods for malaria diagnosis. 25 However, although malaria-disease burden in malaria-endemic settings such as Uganda is largely concentrated in infants and young children, the substantial burden of P falciparum infection among patients with COVID-19 who were older than 60 years of age in this study is intriguing and requires further investigation.…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of malaria in this cohort is similar to population-level regional estimates in the country, as shown by studies that used molecular methods for malaria diagnosis. 25 However, although malaria-disease burden in malaria-endemic settings such as Uganda is largely concentrated in infants and young children, the substantial burden of P falciparum infection among patients with COVID-19 who were older than 60 years of age in this study is intriguing and requires further investigation.…”
Section: Discussionmentioning
confidence: 86%
“…It is difficult to completely exclude the possibility of current or very recent malaria infection in children living in endemic areas. The presence of PCR detectable parasites may vary from day to day over weeks or months of follow up in individual children (40,41). Children can maintain the same (genetically identical) parasite infection for many months with parasites only being intermittently detectable by microscopy and PCR (41,42) and the density of subclinical infections can vary through time with windows of undetectable parasitaemia (41).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of PCR detectable parasites may vary from day to day over weeks or months of follow up in individual children (40,41). Children can maintain the same (genetically identical) parasite infection for many months with parasites only being intermittently detectable by microscopy and PCR (41,42) and the density of subclinical infections can vary through time with windows of undetectable parasitaemia (41). Moreover, a recent study has revealed a hidden biomass of parasites in the spleens of patients undergoing splenectomy, including some patients in whom no circulating parasites could be detected (43).…”
Section: Discussionmentioning
confidence: 99%
“…The review found intermittent preventive treatment to be well tolerated and acceptable to communities. School-aged children are significant reservoirs of human-to-mosquito transmission 35 37 . There is some evidence that administration of intermittent preventive treatment to school-age children can confer a community-level benefit to those not receiving intermittent preventive treatment.…”
Section: Discussionmentioning
confidence: 99%